2016
DOI: 10.1002/jcla.22042
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Parameters of Complete Blood Count With Different Storage Conditions

Abstract: This study shows that most parameters of the CBC are unaffected with the studied storage temperature up to 48 hr except for the PLT which should be performed within 6 hr of the post-collection time. To avoid changes in a few parameters such as Htc, it is best to store the sample at 4 ± 2°C if any delay is anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 9 publications
5
33
1
2
Order By: Relevance
“…Our result of HCT was stable up to 54 h that is similar to other studies at 4°C [6,15,17,19,20]. Result of MCV was found to be stable up to 42 h, regarding result for MCV at 4°C, previous studies are also show supporting with our findings [5,6,15,20,21].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our result of HCT was stable up to 54 h that is similar to other studies at 4°C [6,15,17,19,20]. Result of MCV was found to be stable up to 42 h, regarding result for MCV at 4°C, previous studies are also show supporting with our findings [5,6,15,20,21].…”
Section: Discussionsupporting
confidence: 91%
“…Result of MCV was found to be stable up to 42 h, regarding result for MCV at 4°C, previous studies are also show supporting with our findings [5,6,15,20,21]. Studies by Turhan et al [5] and Lippi et al [2] demonstrated increment was observed on the second day due to reflect the swelling of RBC at room temperature.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations